1981
DOI: 10.1002/ardp.19813140304
|View full text |Cite
|
Sign up to set email alerts
|

Fluorometrische Bestimmung einiger 1,4‐Benzodiazepine

Abstract: Einige pharmazeutisch interessante 1.4-Benzodiazepine konnen nach Behandlung mit Zink/Salzsaure durch Umsetzung mit o-Phthalaldehyd in fluoreszierende Produkte iiberfiihrt werden. Dies ermoglicht die fluorometrische Bestimmung von Oxazepam, Lorazepam, Dikaliumchlorazepat, Demoxepam und Chlordiazepoxid wie sie fur Nitrazepam bekannt ist. Die Zuverlassigkeitskriterien des Verfahrens werden am Beispiel Oxazepam demonstriert. Fluorometric Determination of some 1,4-Benzodiazepines Some pharmaceutically interesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The recording of absorption spectrum for different agents used showed that the first band is due to oxine and this reagent does not show any significant absorbance at the analytical wavelength. The native fluorescence of BZPs is very low and a suitable signal intensity is only obtained either by cyclization to acridines after hydrolysis to benzophenones, [20] thermal heating in acidic solvent, [37] photochemical degradation, [38] derivatization with phthalaldehyde and fluorescamine, [39] or by reduction of the target compounds with Zn • /HCl to form highly fluorescent derivatives. [40] Native fluorescence of some BZPs in acidic or methanolic KOH solution was also reported.…”
Section: Resultsmentioning
confidence: 99%
“…The recording of absorption spectrum for different agents used showed that the first band is due to oxine and this reagent does not show any significant absorbance at the analytical wavelength. The native fluorescence of BZPs is very low and a suitable signal intensity is only obtained either by cyclization to acridines after hydrolysis to benzophenones, [20] thermal heating in acidic solvent, [37] photochemical degradation, [38] derivatization with phthalaldehyde and fluorescamine, [39] or by reduction of the target compounds with Zn • /HCl to form highly fluorescent derivatives. [40] Native fluorescence of some BZPs in acidic or methanolic KOH solution was also reported.…”
Section: Resultsmentioning
confidence: 99%